Simultaneously Tuning Band Structure and Oxygen Reduction Pathway toward High‐Efficient Photocatalytic Hydrogen Peroxide Production Using Cyano‐Rich Graphitic Carbon Nitride - Chen, Lei; Chen, Cheng; Yang, Zhi; Li, Shan; Chu, Chiheng; Chen, Baoliang (Advanced functional materials, 2021)
The demands for green production of hydrogen peroxide have triggered extensive studies in the photocatalytic synthesis, but most photocatalysts suffer from rapid charge recombination and poor 2e− oxygen reduction reaction (ORR) selectivity. Here, a novel composite photocatalyst of cyano‐rich graphitic carbon nitride g‐C3N4 is fabricated in a facile manner by sodium chloride‐assisted calcination on dicyandiamide. The obtained photocatalysts exhibit superior activity (7.01 mm h−1 under λ ≥ 420 nm, 16.05 mm h−1 under simulated sun conditions) for H2O2 production and 93% selectivity for 2e− ORR, much higher than that of the state‐of‐the‐art photocatalyst. The porous g‐C3N4 with Na dopants and cyano groups simultaneously optimize two limiting steps of the photocatalytic 2e− ORR: photoactivity, and selectivity. The cyano groups can adjust the band structure of g‐C3N4 to achieve high activity. They also serve as oxygen adsorption sites, in which local charge polarization facilitates O2 adsorption and protonation. With the aid of Na+, the O2 is reduced to produce more superoxide radicals as the intermediate products for H2O2 synthesis. This work provides a facile approach to simultaneously tune photocatalytic activity and 2e− ORR selectivity for boosting H2O2 production, and then paves the way for the practical application of g‐C3N4 in environmental remediation and energy supply. Two limiting steps in photocatalytic hydrogen peroxide synthesis are simultaneously optimized using porous g‐C3N4 with Na dopants and cyano groups. The CN adjusts the band structure, and serves as oxygen adsorption and reduction sites, with the aid of Na+, to generate superoxide radicals as intermediates for H2O2 production, achieving a high H2O2 generation rate (7.01 mm h−1) and selectivity (93%).